Ultrastructural changes in the common carotid artery in terms of age and gender-related in Rat model - Nejat Ünlükal (Revista Científica)
Sex-related differences were investigated in ultrastructural modifications that occur with ageing in the rat carotid artery in the study. As ageing impacts every system and organ within the human body, it also impacts the circulatory system. The circulatory system serves various functions in the body such as nourishing organs and tissues, oxygenating and eliminating toxic substances. A condition like atherosclerosis or thrombosis in the circulatory system results in permanent harm to structures like the central nervous system, heart and even fatality. Although the pathologies observed in the vessels are commonly attributed to the generation of atheromas, it has been recognised in recent years that changes in the tunica intima and tunica media lead to impaired vascular function without the formation of atheromas. Despite the long-standing belief that women have a advantage in age-related cardiovascular diseases, there has been no ultrastructural examination to support this theory. We explored the sex-related discrepancies in the ultrastructural modifications produced by aging in the carotid artery. A total of 28 Sprague-Dawley rats, 14 males and 14 females, were planned to be used in the study. Of these 28 rats, 4 females and 4 males was constitute the control group. The rats in the control group was approximately 10 weeks old, and the rats in the experimental group, which was represent the aged group, was 19 weeks old. All animals in the study were anaesthetised and then sacrificed by removal of the heart. The right and left common carotid arteries were removed from the sacrificed animals. Collected vessels prepared for Transmission Electron Microscopy (TEM) examination. For each animal, at least four TEM images were taken from four different sections from the same block. As a result, the impact of vascular ageing manifested as apoptosis and age-related dysfunction in endothelial cells, thickening of the subendothelial layer, elastin deterioration, collagen deposition in the matrix, and degradation of the internal elastic lamina. Notably, vascular degeneration is more severe in men than in women. It is clear that the endothelium is subject to accumulated damage with age. We believe that the dissimilarity between males and females is attributed to the estrogen’s proliferative and anti-inflammatory impact.